2011
DOI: 10.1016/j.jbi.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Toward automated consumer question answering: Automatically separating consumer questions from professional questions in the healthcare domain

Abstract: Objective Both healthcare professionals and healthcare consumers have information needs that can be met through the use of computers, specifically via medical question answering systems. However, the information needs of both groups are different in terms of literacy levels and technical expertise, and an effective question answering system must be able to account for these differences if it is to formulate the most relevant responses for users from each group. In this paper, we propose that a first step towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(24 reference statements)
0
19
0
2
Order By: Relevance
“…Previous work has shown that professional questions are shorter, 14 but we have demonstrated that professionals ask more succinct questions: fewer sentences, fewer subquestions, and less background information. Compare the WEBC question about bipolar disorder in Figure 1(a) to the PHST question in Figure 1(b).…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Previous work has shown that professional questions are shorter, 14 but we have demonstrated that professionals ask more succinct questions: fewer sentences, fewer subquestions, and less background information. Compare the WEBC question about bipolar disorder in Figure 1(a) to the PHST question in Figure 1(b).…”
Section: Discussionmentioning
confidence: 45%
“…Among similar resources, the divide was smaller: QA websites had some variation (37-100 versus 11-36), while the NLM questions varied little (70 versus 62). On the other hand, point-of-care questions, for which we have no comparable consumer corpus, were quite short (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and forum questions, for which we have no comparable professional corpus, were quite long (106). Similar effects can be seen with sentences, where most professional questions had 1 or 2 sentences (except NLMP), while consumer questions tended to have 3 or more (2.8-6.9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [6] juga mengembangkan model mesin pembelajaran untuk klasifikasi otomatis antara pertanyaan konsumen dan pertanyaan profesional. Untuk mengevaluasi ketahanan model, Liu et al menguji model yang di gunakan langsung oleh konsumen pada PointCare dataset untuk konsumen dan praktek online dataset.…”
Section: Pendahuluanunclassified